MOTIVASI KERJA DENGAN KINERJA KERJA PADA KARYAWAN BAGIAN GUDANG PT. X KOTA BATANG - Putu fahriza dwila saputra; Christiana hari soetjiningsih (Bajang Institute, 2023)
This study aims to determine the relationship between work motivation and employee work performance at the warehouse employees of PT. X Batang city. Participants are employees of PT. X Batang city with a total of 40 people. Data collection uses a work motivation scale consisting of 26 items and a work productivity scale consisting of 21 items and both have met the requirements of good reliability. Data analysis using Pearson product moment correlation technique. The results of this study indicate a correlation coefficient of 0.866 with a significance value of 0.000 (p < 0.05), meaning that there is a significant positive relationship between work motivation and work performance on employees of PT. X Batang city. The higher the work motivation, the higher the work performance, and conversely the lower the work motivation, the lower the work performance. Through this research is expected to help companies in an effort to increase work productivity, one of which is by maintaining and emphasizing work motivation so that employees at PT. X Batang city still has high employee work performance.